Clots Are Potent Triggers of Inflammatory Cell Gene Expression: Indications for Timely Fibrinolysis. Issue 10 (October 2017) - Campbell, Robert A.; Vieira-de-Abreu, Adriana; Rowley, Jesse W.; Franks, Zechariah G.; Manne, Bhanu Kanth; Rondina, Matthew T.; Kraiss, Larry W.; Majersik, Jennifer J.; Zimmerman, Guy A.; Weyrich, Andrew S.
Abstract : Objective—: Blood vessel wall damage often results in the formation of a fibrin clot that traps inflammatory cells, including monocytes. The effect of clot formation and subsequent lysis on the expression of monocyte-derived genes involved in the development and progression of ischemic stroke and other vascular diseases, however, is unknown. Determine whether clot formation and lysis regulates the expression of human monocyte-derived genes that modulate vascular diseases. Approach and Results—: We performed next-generation RNA sequencing on monocytes extracted from whole blood clots and using a purified plasma clot system. Numerous mRNAs were differentially expressed by monocytes embedded in clots compared with unclotted controls, and IL-8 (interleukin 8) and MCP-1 (monocyte chemoattractant protein-1) were among the upregulated transcripts in both models. Clotted plasma also increased expression of IL-8 and MCP-1, which far exceeded responses observed in lipopolysaccharide-stimulated monocytes. Upregulation of IL-8 and MCP-1 occurred in a thrombin-independent but fibrin-dependent manner. Fibrinolysis initiated shortly after plasma clot formation (ie, 1–2 hours) reduced the synthesis of IL-8 and MCP-1, whereas delayed fibrinolysis was far less effective. Consistent with these in vitro models, monocytes embedded in unresolved thrombi from patients undergoing thrombectomy stained positively for IL-8 and MCP-1. Conclusions—: These findings demonstrate that clots are potent inducers of monocyte gene expression and that timely fibrinolysis attenuates inflammatory responses, specifically IL-8 and MCP-1. Dampening of inflammatory gene expression by timely clot lysis may contribute to the clinically proven efficacy of fibrinolytic drug treatment within hours of stroke onset. Abstract : Supplemental Digital Content is available in the text.